DOI: 10.11606/d.23.2006.tde-20092006-092828
|View full text |Cite
|
Sign up to set email alerts
|

"A oximetria de pulso como recurso auxiliar na determinação da vitalidade pulpar de dentes permanentes traumatizados"

Abstract: Ao meu orientador Celso Luiz Caldeira pela orientação e confiança. Ao Professor Antonio Carlos Bombana pelos momentos de aprendizado, incentivo e apoio emocional, na minha vida particular e acadêmica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
2

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
1
1
0
2
Order By: Relevance
“…Because of the direct vitality assessment, rather than the indirect evaluation by nerve fiber stimulation, it may be superior to thermal or electric pulp testing for the judgment of the pulpal status. The mean pulpal oxygen saturation levels found in this investigation were similar to those described by other studies for clinically healthy teeth with and without pulp inflammation (17,20). Several studies that included pediatric and adult participants reported pulp oxygenation values for healthy pulps of around 80% (38,39).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because of the direct vitality assessment, rather than the indirect evaluation by nerve fiber stimulation, it may be superior to thermal or electric pulp testing for the judgment of the pulpal status. The mean pulpal oxygen saturation levels found in this investigation were similar to those described by other studies for clinically healthy teeth with and without pulp inflammation (17,20). Several studies that included pediatric and adult participants reported pulp oxygenation values for healthy pulps of around 80% (38,39).…”
Section: Discussionsupporting
confidence: 89%
“…It was shown that PO is a safe and reliable method to identify devitalized teeth (15)(16)(17)(18). Several authors hinted that PO potentially may be useful to identify the different stages of the pathologic processes affecting the pulp (15)(16)(17). However, so far, there are no concrete data available showing the differences between the various stages of pulp inflammation determined by PO.…”
mentioning
confidence: 99%
“…A utilização do OP como uma ferramenta objetiva para a determinação da vitalidade do tecido pulpar já se mostrou bastante efetiva e segura, principalmente, em casos relacionados a traumatismos dentários como descrito e demonstrado por Schnetter e Wallace (1991); Abrão (2006) e Gopikrishna et al (2007a). De maneira que, muito semelhante ao que ocorre nestes casos, os pacientes submetidos ao tratamento oncológico, através de RT externa, tem geradas injúrias químicas, as quais podem comprometer os tecidos saudáveis e, possivelmente, acarretar alterações microcirculatórias.…”
Section: Discussionunclassified
“…vários processos patológicos podem influenciar na sensibilidade dos nervos pulpares; frente a isto,Reiss e Furedi (1933) sugeriram uma maior resistência das fibras às afecções patológicas.Porém, em 1970, Mullaney et al concluíram que era improvável que as fibras nervosas pulpares resistissem à necrose como especulado no passado. determinar a vitalidade de dentes que haviam sofrido luxação lateral e não respondiam ao teste com gás refrigerante, após duas semanas do trauma,Abrão (2006) analisou os valores de %SpO 2 em três períodos diferentes. Os resultados obtidos demonstraram a correlação entre os níveis de %SpO 2 mensurados no dedo, no dente traumatizado e no dente controle.…”
unclassified